Ultrasonic investigation of fibre texture in plants - H. GAWDA; J. LEWANDOWSKI (Archives of Acoustics, 2015)
The propagation velocities of an ultrasonic dilatational wave in different segments of a cereal stalk were measured and the averaged orientations of crystallites in the same segments were determined applying X-ray diffraction method. Using the principle of maximum entropy the analytical form of the probability density function of the crystallite orientation in a segment was found for the different values of the propagation velocity observed. Subsequently the fractions of crystallites with orientation angles lying in a given finite angle interval were calculated for the arbitrarily chosen propagation velocities.